Craft work. Cultural value and global influence - Acosta Marquez, Maria Pilar (2021)
The craft work is the result of a process of cultural preservation through the manual elaboration of artifacts with ethnic and artistic characteristics. However, craft work is seen as vulnerable to a strong competitor backed by mass culture, the effect of globalization. Craftsmanship and globalization are facing a battle where the damaging effects will be concentrated in the displacement of this cultural activity, in its economy and in the perception of society about it. This work presents the current framework of craftsmanship and data from the artisan sector in Mexico, with the aim of reflecting on the effects of globalization and reconsider our homogeneous cultural and plastic consumption.